Molecular dynamics simulations of pure methane and carbon dioxide hydrates: lattice constants and derivative properties. (16th September 2016) - Costandy, Joseph; Michalis, Vasileios K.; Tsimpanogiannis, Ioannis N.; Stubos, Athanassios K.; Economou, Ioannis G.
ABSTRACT: We report extensive molecular dynamics simulation results of pure methane and carbon dioxide hydrates at pressure and temperature conditions that are of interest to various practical applications. We focus on the calculation of the lattice constants of the two pure hydrates and their dependence on pressure and temperature. The calculated lattice constants are correlated using second order polynomials which are functions of either temperature or pressure. Finally, the obtained correlations are used in order to calculate two derivative properties, namely the isothermal compressibility and the isobaric thermal expansion coefficient. The current simulation results are also compared against reported experimental measurements and other simulation studies and good agreement is found for the case of isothermal compressibility. On the other hand, for the case of isobaric thermal expansion coefficient good agreement is found only with other simulation studies, while the simulation studies are in disagreement with experiments, particularly at low temperatures. Abstract :